Suptavumab for the Prevention of Medically Attended Respiratory Syncytial Virus Infection in Preterm Infants. (8th September 2020) - Simões, Eric A F; Forleo-Neto, Eduardo; Geba, Gregory P; Kamal, Mohamed; Yang, Feng; Cicirello, Helen; Houghton, Matthew R; Rideman, Ronald; Zhao, Qiong; Benvin, Sarah L; Hawes, Alicia; Fuller, Erin D; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is a major cause of childhood medically attended respiratory infection (MARI). Methods: We conducted a randomized, double-blind, placebo-controlled phase 3 trial in 1154 preterm infants of 1 or 2 doses of suptavumab, a human monoclonal antibody that can bind and block a conserved epitope on RSV A and B subtypes, for the prevention of RSV MARI. The primary endpoint was proportion of subjects with RSV-confirmed hospitalizations or outpatient lower respiratory tract infection (LRTI). Results: There were no significant differences between primary endpoint rates (8.1%, placebo; 7.7%, 1-dose; 9.3%, 2-dose). Suptavumab prevented RSV A infections (relative risks, .38; 95% confidence interval [CI], .14–1.05 in the 1-dose group and .39 [95% CI, .14–1.07] in the 2-dose group; nominal significance of combined suptavumab group vs placebo; P = .0499), while increasing the rate of RSV B infections (relative risk 1.36 [95% CI, .73–2.56] in the 1-dose group and 1.69 [95% CI, .92–3.08] in the 2-dose group; nominal significance of combined suptavumab group vs placebo; P = .12). Sequenced RSV isolates demonstrated no suptavumab epitope changes in RSV A isolates, while all RSV B isolates had 2–amino acid substitution in the suptavumab epitope that led to loss of neutralization activity. Treatment emergent adverse events were balanced across treatment groups. Conclusions: Suptavumab did not reduce overall RSV hospitalizations or outpatient LRTI because of a newly circulating mutant strain of RSV B. Genetic variation in circulating RSV strains will continue to challenge prevention efforts. Clinical Trials Registration: NCT02325791. Abstract : In a randomized, double-blind, placebo-controlled phase 3 trial in 1154 preterm infants, 1 or 2 doses of suptavumab did not reduce overall respiratory syncytial virus (RSV) hospitalizations or outpatient LRTI because of a newly circulating mutant strain of RSV-B.